2010
DOI: 10.1002/jbmr.311
|View full text |Cite
|
Sign up to set email alerts
|

BMP-9-induced muscle heterotopic ossification requires changes to the skeletal muscle microenvironment

Abstract: Heterotopic ossification (HO) is defined as the formation of bone inside soft tissue. Symptoms include joint stiffness, swelling, and pain. Apart from the inherited form, the common traumatic form generally occurs at sites of injury in damaged muscles and is often associated with brain injury. We investigated bone morphogenetic protein 9 (BMP-9), which possesses a strong osteoinductive capacity, for its involvement in muscle HO physiopathology. We found that BMP-9 had an osteoinductive influence on mouse muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
113
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(119 citation statements)
references
References 52 publications
5
113
1
Order By: Relevance
“…We have recently performed experiments showing muscle paralysis inhibits BMP-4-induced HO in the same mouse model (data not shown). Although we have not specifically confirmed that muscle paralysis would inhibit HO induced primarily by other known osteogenic cytokines such as BMP-1, BMP-9 or transforming growth factor-b [15,18], our findings that paralysis inhibits pathologic bone formation during fracture, an osteogenic response induced by a complex signaling cascade, further suggests that this inhibitory therapy may be used regardless of the specific underlying signaling impetus. Additionally, the ability to inhibit HO formation in the BMP-2 model is primarily based on a priori knowledge of where and when HO formation will occur, similar to the clinical conditions after THA or acetabular fracture repair.…”
Section: Discussioncontrasting
confidence: 61%
“…We have recently performed experiments showing muscle paralysis inhibits BMP-4-induced HO in the same mouse model (data not shown). Although we have not specifically confirmed that muscle paralysis would inhibit HO induced primarily by other known osteogenic cytokines such as BMP-1, BMP-9 or transforming growth factor-b [15,18], our findings that paralysis inhibits pathologic bone formation during fracture, an osteogenic response induced by a complex signaling cascade, further suggests that this inhibitory therapy may be used regardless of the specific underlying signaling impetus. Additionally, the ability to inhibit HO formation in the BMP-2 model is primarily based on a priori knowledge of where and when HO formation will occur, similar to the clinical conditions after THA or acetabular fracture repair.…”
Section: Discussioncontrasting
confidence: 61%
“…Other trauma-associated models include the use of BMPs in combination with cardiotoxin (CTX) or physical damage induced by crushing the muscle with surgical tweezers. 23 It has been difficult to induce HO with trauma alone, although a recently developed model using blast amputation holds promise. 24 In the studies reported here we set out to develop a new murine model of traumatic HO that more closely mimics the formation of heterotopic bone associated with blunt physical muscle trauma such as occurs in accidents or injuries in a military setting.…”
mentioning
confidence: 99%
“…(3,(6)(7)(8) However, the cellular and molecular mechanisms that are activated through these tissue changes remain largely undetermined. In this issue of the Journal of Bone and Mineral Research, Leblanc and colleagues (9) move us a step closer to being able to elucidate factors within the cellular environment that regulate cell differentiation to form bone tissue through their study investigating potential osteoprogenitor cells and requirements for specific tissue microenvironments that contribute to the pathophysiology of BMP-induced heterotopic ossification. Their approach used a series of in vitro and in vivo assays and implicates BMP-9 acting through the ALK1 BMP type 1 receptor as an inducer of muscle-resident stromal cells (mrSCs) to undergo osteogenesis and to form heterotopic bone tissue.…”
mentioning
confidence: 99%